2011
DOI: 10.1021/jo101886s
|View full text |Cite
|
Sign up to set email alerts
|

Chemoselective C-4 Aerobic Oxidation of Catechin Derivatives Catalyzed by the Trametes villosa Laccase/1-Hydroxybenzotriazole System: Synthetic and Mechanistic Aspects

Abstract: Catechin derivatives were oxidized in air in the presence of the Trametes villosa laccase/1-hydroxybenzotriazole (HBT) system in buffered water/1,4-dioxane as reaction medium. The oxidation products, flavan-3,4-diols and the corresponding C-4 ketones, are bioactive compounds and useful intermediates for the hemisynthesis of proanthocyanidins, plant polyphenols which provide beneficial health properties for humans. Determinations of oxidation potentials excluded that catechin derivatives could be directly oxidi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
21
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(24 citation statements)
references
References 105 publications
3
21
0
Order By: Relevance
“…The laccase-HBT system can also achieve better removal of non-phenolic compounds as the aminoxyl radicals have redox potentials in the order of 1.0-1.1 V (d' Acunzo et al, 2006), which are higher than that of laccase only (0.17V) (Klonowska et al, 2002). For instance, Bernini et al (2011) reported that the laccase-mediator system can effectively trigger the H-abstraction from benzylic carbons of nonphenolic compounds. This can explain the improvement in atrazine, amitriptyline and ametryn removal in the current study in the presence of HBT.…”
Section: [Figure 5]mentioning
confidence: 99%
“…The laccase-HBT system can also achieve better removal of non-phenolic compounds as the aminoxyl radicals have redox potentials in the order of 1.0-1.1 V (d' Acunzo et al, 2006), which are higher than that of laccase only (0.17V) (Klonowska et al, 2002). For instance, Bernini et al (2011) reported that the laccase-mediator system can effectively trigger the H-abstraction from benzylic carbons of nonphenolic compounds. This can explain the improvement in atrazine, amitriptyline and ametryn removal in the current study in the presence of HBT.…”
Section: [Figure 5]mentioning
confidence: 99%
“…5,7,3 0 ,4 0 -Tetramethoxyflavanone (methylated hesperetin)(15) Yield: 88%; colorless oil; spectroscopic data are according to those reported in the literature 29. 5,7,3 0 ,4 0 -Tetramethoxycatechin(21) Yield: 92%; yellow oil; spectroscopic data are according to those reported in the literature 30. 5,7,3 0 ,4 0 -Tetramethoxyepicatechin(26) Yield: 90%; yellow oil; spectroscopic data are according to those reported in the literature 30.…”
mentioning
confidence: 91%
“…Trimethoxyflavanone (methylated naringenin) 12; 5,7,3 0 ,4 0tetramethoxyflavanone (methylated hesperetin) 15; 5,7,3 0 ,4 0tetramethylcatechin 21 and 5,7,3 0 ,4 0 -tetramethylepicatechin 26 were prepared as already reported by us 29,30. 5,7,4 0 -Trimethoxyflavanone (methylated naringenin)(12) Yield: 90%; colorless oil; spectroscopic data are according to those reported in the literature 29.…”
mentioning
confidence: 99%
“…Antibiotics, metal ions, and various quaternary ammonium compounds are being used worldwide though these antimicrobial compounds are also being claimed to be associated with antibiotic resistance, complex chemical synthesis, environmental pollution, and high cost [3,4]. However, natural antibacterial agents have been recently identified to overcome these disadvantages [5]. Marine organisms are one of the richest sources of bioactive compounds and chemical diversity [6,7].…”
Section: Introductionmentioning
confidence: 99%